2019
DOI: 10.1029/2018ea000517
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Fractionation in Photolysis of Ozone in the Hartley and Chappuis Bands

Abstract: The isotopic enhancement of atmospheric ozone (O3) is mainly determined by two processes of formation and photolytic decomposition. The formation is known to be associated with isotopic fractionation which can be as high as 120‰ relative to the parent oxygen. Photolysis‐induced isotopic fractionation in O3, however, is not known accurately. Absorption cross sections of various ozone species have been calculated by Zero Point Energy‐based model and quantum mechanical wave packet model. But their predictions per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Isotope effects in other reactions (e.g., during O 3 photolysis or chemical destruction) may also be important, but their cumulative effects on 16 O 18 O and 18 O 18 O‐containing species in the atmosphere are poorly known. Owing to the uncertainties in these quantities (Früchtl, Janssen, Rockmann, 2015, Früchtl, Ianssen, Taraborrelli, et al., 2015; Huang et al., 2019; Liang et al., 2006), this model only explores the relationship between the isotope effects for O( 3 P ) + O 2 isotope exchange and O 3 formation. We acknowledge that the results obtained are necessarily incomplete, although they are still informative and relevant to the global atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Isotope effects in other reactions (e.g., during O 3 photolysis or chemical destruction) may also be important, but their cumulative effects on 16 O 18 O and 18 O 18 O‐containing species in the atmosphere are poorly known. Owing to the uncertainties in these quantities (Früchtl, Janssen, Rockmann, 2015, Früchtl, Ianssen, Taraborrelli, et al., 2015; Huang et al., 2019; Liang et al., 2006), this model only explores the relationship between the isotope effects for O( 3 P ) + O 2 isotope exchange and O 3 formation. We acknowledge that the results obtained are necessarily incomplete, although they are still informative and relevant to the global atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…See later sections for details. To check the validity of the adopted fractionations, we compare the calculated values with recently measured numbers at several wavelengths in the Chappuis band [30][31][32].…”
Section: Pressure Photolysis Cloudmentioning
confidence: 99%
“…Photolysis of ozone occurs primarily in the Hartley and Huggins bands in the UV and Chappuis bands at longer wavelengths (450-850 nm). Chappuis band photolysis dominates for altitudes <35 km and could deplete heavy ozone [5,31,32,[41][42][43]. Due to limited photolytic data for major isotopolocules of ozone in the visible band [31,32,44], we followed typical theories to estimate the fractionation.…”
Section: Chappuis Band Photolysismentioning
confidence: 99%
“…82 It is now well established [4][5][6] that the ozone MIF is not a minor and exotic phenomenon of a limited impact: its effect is photochemically transferred to many oxygen-bearing species including atmospheric CO 2 , O 2 , and water in the early solar system. 6,91,92 There is a wide area of interdisciplinary scientific fields, including atmospheric physics, geo-and cosmochemistry or climate research, 5,[93][94][95][96][97] where the ozone isotope composition, or molecular effects of isotope fractionation, plays a major role. [98][99][100] The state-of-the art of the MIF studies and possible impacts across various branches of science have been described in recent exhaustive reviews by Thiemens and Lin, 5 Thiemens et al, 20 Dauphas and Schauble, 4 and Carlstad and Boering, 6 who have concluded that ''The origin in chemical physics of the large, robustly measured mass-independent enrichments in ozone resulting from the three-body ozone formation reaction remains elusive and represents an intriguing chemical physics puzzle that deserves further study''.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established 4–6 that the ozone MIF is not a minor and exotic phenomenon of a limited impact: its effect is photochemically transferred to many oxygen-bearing species including atmospheric CO 2 , O 2 , and water in the early solar system. 6,91,92 There is a wide area of interdisciplinary scientific fields, including atmospheric physics, geo- and cosmochemistry or climate research, 5,93–97 where the ozone isotope composition, or molecular effects of isotope fractionation, plays a major role. 98–100…”
Section: Introductionmentioning
confidence: 99%